Phasmagraphy: A potential future for artistic imaging - Reinhuber, Elke (2018)
In recent years, a rising interest in scientific imaging has become apparent, in art production and in thematic exhibitions, as well as in popular media and advertising. Images captured by, and supposedly read through, machines open up a new era – not only for an as-yet-undefined aesthetic journey, but also to reveal insight into a normally invisible layer of reality. A wide range of techniques is already well established – not only in science, but also in an artistic context. Based on an overview of different media and their applications, the term phasmagraphy is introduced to be applied to the expanded boundaries of the visible photographic spectrum to the adjacent wavelengths beyond full-spectrum photography.